Lazer na Comunidade Quilombola de Córrego do Franco - PR e suas interlocuções com a religiosidade local - Rangel, Renato Alexandre (2013)
This research focuses on the relationship between leisure, religiosity and the Quilombola communities in order to analyze the leisure in a Quilombola community in Parana - Quilombola community of Corrégo do Franco - and its dialogues with the local religiosity. Specifically, the investigation sought to elucidate whether there is influence of leisure in the exercise of religious life by the Quilombolas and, at the same time, if there is influence of local religiosity in ways of experiencing leisure. Since then, we tried to discuss about the possible implications of the relationship between leisure and religion in shaping the everyday life of the investigated Quilombola community. Therefore, it was necessary to combine incursions by the literature on the topic with immersions in the field through the development of ethnographic case study (ANDRE, 1995), which made it possible to capture dimensions of the everyday life of the investigated Quilombola community concerning leisure and religion, by the use of intensive observation techniques, daily field notes and semi- structured interviews. Since the Pentecostal Protestant religion is densely expressed in the Quilombola community of Corrégo do Franco, especially by the presence of four churches - Assembleia de Deus, Assembleia de Cristo dos Heróis Missionários, Redenção e Congregração Cristã do Brasil - it emphasizes the direct influence of this religion in the everyday life of this community and, consequently, in the field of leisure. On one hand, the Pentecostal church is taken as a recreational place by the Quilombola adults, in view of the centrality it assumes in their lives, dissolving interests for several leisure practices that may emanate from the community or be addressed to it. On the other hand, there are considerable leisure practices integrating the everyday life of young people, who are not motivated by the church and seek the aspirations of their own time and the communication processes of their generation in the experience of leisure. That is set by the force of religion in the community that overlaps the leisure, and by small spaces of resistance to religious normative process that prevents or hinders the experience of leisure. This points towards gaps in relation to the understanding of leisure as a social right, to be built by all participants in an intergenerational perspective, with the participation of different departments of society and of the federal, state and/or local government, in order to contribute with improvements in the living conditions of the Quilombola population, that will turn into improvements to the Quilombola subject.